Gestión administrativa-financiera y su incidencia en la responsabilidad social empresarial, de la empresa sorti cantón Quevedo, año 2023 - Alcívar Álvarez, Dunia Margarita (2025)
The study examines the interdependence between administrative-financial management and Corporate Social Responsibility (CSR), grounded in theories such as Carroll’s CSR Pyramid and Porter’s Shared Value Model. The objective was to assess how administrative-financial management impacts SORTI’s CSR, analyzing its financial situation, describing its CSR practices, and proposing guidelines to optimize the synergy between profitability and sustainability. A mixed-method approach was employed, incorporating descriptive, explanatory, correlational, and applied research. Deductive and inductive methods, semi-structured interviews with executives, and surveys of 155 active users during the research period were used, with selection based on non-probabilistic convenience sampling considering willingness to participate. SORTI demonstrated dynamic monthly income behavior, ranging from $900.25 to a maximum of $5,819.12, but faces critical liquidity issues (fund retention rate: 53.98%), payment delays, and dependence on its Manta headquarters, limiting its autonomy. Its CSR practices, focused on paper reduction and anti-gambling addiction policies, are reactive and lack measurable community impact, with 89.7% of users unaware of these initiatives. Although financial management is perceived as efficient (69% positive perception), it prioritizes profitability over social investment, according to 58.7% of respondents. The correlation between financial management and CSR is positive (Rho=0.981, p<0.001). Recommendations include implementing automated financial indicators, creating a community fund from profits, developing a CSR manual, and launching social media campaigns to promote anti-gambling addiction policies.